استراتيجيَّة الاستعمار الفرنسي في تفكيك القبائل الجزائريَّة خلال القرن التَّاسع عشر ميلادي وآثارها ( قبائل الحدود الشَّرقيَّة أنموذجاً) - (:unkn) unknown (University of Eloued جامعة الوادي, 2021)
عرفت القبيلة في الجزائر تغيُّرات عدَّة إبَّان فترة الاستعمار الفرنسي للجزائر، وذلك بفعل جملة القوانين والمراسيم التي سنّتها إدارة الاحتلال عبر محطَّات زمنيَّة متباينة بدءاً من سنة 1840م إلى غاية سنة 1873م وما بعدها، والتي ضربت البنية القبليَّة، عبر تفكيكها وإعادة تركيبها وفق استراتيجيَّات تتلاءم ورغبة الاستعمار في التَّفرقة و التَّوطين والتَّملك، وهو ما كان له بالغ الأثر على مختلف القبائل الجزائريَّة وخاصة منها القبائل الحدوديَّة. Abstract: The tribe in Algeria witnessed many change during the French colonial period, through the set of laws enacted by the occupation administration through different time stations starting from the year 1840CE to1870CE,with had an impact on the social structure in Algeria through the dispersion of the previous structure and the restoration of Its composition according to strategies compatible with the French colonial desire to resettle and acquire ownership, with had disastrous consequences for the Algerian tribes through disassociation and settlement ofdisputes and discrimination ,especially those border tribes.
مقال